Correlation Parents' Knowledge and Environmental Sanitation Towards The Helminthiasis in Students - Najmii, Muhammad Firoos Allaam; Bestari, Rochmadina Suci; Aisyah, Riandini; Rahmah, Maulida (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The objective of this study is to determine whether parental knowledge about worms and environmental sanitation are related to the incidence of worms (helminthiasis) among students in SDN 02 Selokaton. Methodology: This study uses an analytical observational study research method with a cross-sectional research design. Results: there is no significant relationship between parental knowledge about worms and the incidence of worm infections, there is no significant relationship between environmental sanitation and the incidence of worm infections. Applications/Originality/Value: The novelty in this study is that no data has been found on the prevalence of worms in elementary school students in Karanganyar, so this study can be an initial screening of the prevalence of worms in elementary school students in Karanganyar.